2023
DOI: 10.3390/ijms24043451
|View full text |Cite
|
Sign up to set email alerts
|

Chondroitin Sulfate-Tyramine-Based Hydrogels for Cartilage Tissue Repair

Abstract: The degradation of cartilage, due to trauma, mechanical load or diseases, results in abundant loss of extracellular matrix (ECM) integrity and development of osteoarthritis (OA). Chondroitin sulfate (CS) is a member of the highly sulfated glycosaminoglycans (GAGs) and a primary component of cartilage tissue ECM. In this study, we aimed to investigate the effect of mechanical load on the chondrogenic differentiation of bone marrow mesenchymal stem cells (BM-MCSs) encapsulated into CS-tyramine-gelatin (CS-Tyr/Ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 54 publications
1
11
0
Order By: Relevance
“…Previously published studies showed the chondrogenic potential of BMMSCs being high enough to be used for the cartilage regeneration purpose in vitro [ 43 , 44 ]. Our recently published findings also confirmed the higher chondrogenic potential of BMMSCs than other MSCs and their suitability for the investigation of chondrogenic differentiation mechanisms in model systems in vitro [ 41 , 45 ]. Human BMMSCs recruitment to the IL-8- and MIP-3α-containing scaffolds enhanced tissue regeneration of an osteochondral defect site in beagle knee articular cartilage [ 46 ].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Previously published studies showed the chondrogenic potential of BMMSCs being high enough to be used for the cartilage regeneration purpose in vitro [ 43 , 44 ]. Our recently published findings also confirmed the higher chondrogenic potential of BMMSCs than other MSCs and their suitability for the investigation of chondrogenic differentiation mechanisms in model systems in vitro [ 41 , 45 ]. Human BMMSCs recruitment to the IL-8- and MIP-3α-containing scaffolds enhanced tissue regeneration of an osteochondral defect site in beagle knee articular cartilage [ 46 ].…”
Section: Discussionsupporting
confidence: 80%
“…The various types of the multipotent and pluripotent stem cells, tissue engineering technologies, including scaffolds or hydrogels, have been investigated for the cartilage tissue regenerating purposes [ 40 , 41 ]. The multipotent MSCs derived from the adipose [ 20 ], human synovial membrane [ 21 ], autologous and allogeneic bone marrow [ 22 , 23 ] and chondrocytes [ 24 , 25 ], umbilical cord [ 26 ] and other tissues in patients and animal models have been investigated for the OA regeneration purposes.…”
Section: Discussionmentioning
confidence: 99%
“…However, adding the CS-Tyr/Gel/BM-MSCs composite downregulated the release of COMP and GAGs. 17 Interestingly, synovial cells from OA mice treated with glycosaminoglycan-based hydrogel incorporated with hyaluronic acid, chondroitin sulfate E disaccharide, and thermosensitive Pluronic F127 (PF-HA-diSE), indicating decreased expression of C5a, C8, C9, and SC5b-9. 18 SW1353 cells stimulated with IL-1β showed increased expression of NF-κB p65 and cyclooxygenase-2 (COX-2), but reduced levels of collagen II.…”
Section: Role Of D Ifferent K Inds Of Hydrog El S In Oa-rel Ated Infl...mentioning
confidence: 99%
“…When OA patients' cartilage explants were incubated in chondrogenic condition and applied stronger mechanical load, the expression of extracellular matrix (ECM) components glycosaminoglycans (GAGs) and proteoglycans was reduced, and cartilage components (cartilage oligomeric matrix protein (COMP) and (GAGs)) were released as compared with not‐compressed OA cartilage explants. However, adding the CS‐Tyr/Gel/BM‐MSCs composite downregulated the release of COMP and GAGs 17 . Interestingly, synovial cells from OA mice treated with glycosaminoglycan‐based hydrogel incorporated with hyaluronic acid, chondroitin sulfate E disaccharide, and thermosensitive Pluronic F127 (PF‐HA‐diSE), indicating decreased expression of C5a, C8, C9, and SC5b‐9 18 .…”
Section: Role Of Different Kinds Of Hydrogels In Oa‐related Inflammat...mentioning
confidence: 99%
See 1 more Smart Citation